Strategy for Strengthening Student Capability through Ecological Counseling Approach in Islamic Elementary Schools - Hidayat Hidayat; Imron Syahroni; Indah Aminatuz Zuhriyah; Yuliana Nur Mustaghfiroh4 (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
The phenomenon of Islamic elementary education shows that Guidance and Counseling services in Islamic Elementary Schools still tend to be oriented towards handling behavioral problems and have not been systematically directed at strengthening students' capabilities for substantive freedom to develop academically, socially, and spiritually. This study aims to analyze strategies for strengthening student capabilities through an ecological counseling approach at SDI Surya Buana, Malang City. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, class teachers, and guidance counselors, participant observation of learning practices and character building, and documentation studies of school programs. Data analysis was conducted thematically through reduction, categorization, and conclusion drawing. The research results show that strengthening student capability occurs through the integration of self-regulation habits in the classroom, school-parent collaboration, a reflective culture based on Islamic values, and preventive-developmental counseling interventions. The ecological approach allows for synergy between the classroom environment, school policies, and family parenting patterns in shaping student agency and resilience. The implications of this research emphasize the importance of developing a systemic, collaborative, and capability-expanding counseling service model for Islamic elementary schools as the foundation for transformative Islamic basic education.